Degradation of 1,2-Dibromoethane by Mycobacterium sp. Strain GP1 - Poelarends, Gerrit J. (American Society for Microbiology, 1999)
The newly isolated bacterial strain GP1 can utilize 1,2-dibromoethane as the sole carbon and energy source. On the basis of 16S rRNA gene sequence analysis, the organism was identified as a member of the subgroup which contains the fast-growing mycobacteria. The first step in 1,2-dibromoethane metabolism is catalyzed by a hydrolytic haloalkane dehalogenase. The resulting 2-bromoethanol is rapidly converted to ethylene oxide by a haloalcohol dehalogenase, in this way preventing the accumulation of 2-bromoethanol and 2-bromoacetaldehyde as toxic intermediates. Ethylene oxide can serve as a growth substrate for strain GP1, but the pathway(s) by which it is further metabolized is still unclear. Strain GP1 can also utilize 1-chloropropane, 1-bromopropane, 2-bromoethanol, and 2-chloroethanol as growth substrates. 2-Chloroethanol and 2-bromoethanol are metabolized via ethylene oxide, which for both haloalcohols is a novel way to remove the halide without going through the corresponding acetaldehyde intermediate. The haloalkane dehalogenase gene was cloned and sequenced. The dehalogenase (DhaA(f)) encoded by this gene is identical to the haloalkane dehalogenase (DhaA) of Rhodococcus rhodochrous NCIMB 13064, except for three amino acid substitutions and a 14-amino-acid extension at the C terminus. Alignments of the complete dehalogenase gene region of strain GP1 with DNA sequences in different databases showed that a large part of a dhaA gene region, which is also present in R. rhodochrous NCIMB 13064, was fused to a fragment of a haloalcohol dehalogenase gene that was identical to the last 42 nucleotides of the hheB gene found in Corynebacterium sp. strain N-1074.